Respostas

2014-02-02T13:51:59-02:00
x² - 2x - 8 = 0
Δ = b² - 4ac
Δ = (-2)² - 4.1.(-8)
Δ = 4 + 32
Δ = 36
x' = (-b + √Δ)/2a
x' = (2 + 6)/2
x' = 4
x'' = (-b - √Δ)/2a
x'' = (2 - 6)/2
x'' = -2
S  = {-2,4}
1 5 1
2014-02-02T15:46:46-02:00
Vamos determinar as raízes:

x²-2x-8

Identifiquemos a, b e c:
a= 1
b= -2
c= -8

Vamos substituir estes valores em bháskara:
Δ=  b²-4.a.c
Δ= (-2)²-4.1.(-8)
Δ= 4+32
Δ= 36
Δ= -b±√Δ
         2.a
Δ= 2±6
      2.1
x'= 2+6
       2
x'= 8
      2
x'=4
x''= 2-6
        2
x''= -4 
        2
x''=-2

S={-2, 4}